Novel magnetic composites based on water soluble unsaturated polyester resin and iron oxide nanoparticles (Fracture and Structural Integrity, 2016)
Magnetic nanocomposites on the basis of water soluble unsaturated polyester resin filled with different amount of iron oxide nanoparticles have been successfully prepared. The mechanical properties of thus prepared composites as tensile, impact and flexural strength were determined. The specific volume and surface resistance of the magnetic nanocomposites were also determined.
Keywords: Magnetic Nanoparticles; Unsaturated Polyester Resin; Copolymerization; Mechanical Properties; Surface Resistance